Culturally Sensitive Primary Care in Indonesia: How Should It Work? - Nugraha, Ryan Rachmad; Claramita, Mora (Faculty of Medicine, Public Health, and Nursing, 2025)
The Need for a Culturally-Sensitive Primary CareAs globalization rises and populations grow, cultures intermingle, prompting us to understand culture in the way we interact with each other, and most importantly, in care and practice. This coins the term “culturally sensitive primary care,” or often referred to cultural competence or cultural humility, which is the ability of providers to understand and respond to patients’ cultural belief, values, and language needs. Embracing this culture is critical for improving patients’ outcomes and reducing health disparities. Studies have shown when care is tailored to patients' cultural context, it leads to better communication and therefore higher patient satisfaction and adherence to treatment, and even enhanced clinical outcomes1,2. Doctors who have been trained on culturally adapted communication were found to be associated with patients who were more satisfied, had better understanding of their condition, and showed improved health indicators, such as blood pressure and glucose. Conversely, when cultural understanding is not considered in interacting with patients, miscommunication may occur, such as misunderstanding due to language barriers or difference in health beliefs, which may result in distrust and poorer health outcomes3.Cultural sensitivity is especially important in primary care, particularly as primary care physicians (PCP) become the patients’ first point of contact within the health system. Patients’ health beliefs and behavior are driven by their culture, and thus failure to acknowledge this phenomenon might lead to missed critical information. For example, cultural practices may influence patients’ behavior and shift away patients from accessing appropriate care. A study proved that the higher Traditional Birth Attendants (TBAs) density in a given area is linked with higher odds of mothers not utilizing cascades of maternal services4. On the other hand, PCPs that are culturally adept may use it to their advantage to improve care. A meta-analysis showed that, across interventions targeting underrepresented adults, those with cultural relevance tailoring significantly improved medication adherence compared with non-tailored approaches5.